2021
DOI: 10.1093/inthealth/ihab061
|View full text |Cite
|
Sign up to set email alerts
|

Understanding patient health-seeking behaviour to optimise the uptake of cataract surgery in rural Kenya, Zambia and Uganda: findings from a multisite qualitative study

Abstract: Background Cataract is a major cause of visual impairment globally, affecting 15.2 million people who are blind, and another 78.8 million who have moderate or severe visual impairment. This study was designed to explore factors that influence the uptake of surgery offered to patients with operable cataract in a free-of-charge, community-based eye health programme. Methods Focus group discussions and in-depth interviews were c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…Moreover, the number of blind children living in developing countries within sub-Saharan Africa is disproportionately high. This disparity is due to a combination of factors including supply chain challenges, limited health infrastructure, access to trained subspecialists, and cultural and social factors that may change healthcare-seeking behavior ( 5 ). Immunization and nutritional supplementation, which are critical to childhood vision health, for conditions such as measles and vitamin A deficiency (VAD), respectively, may vary between and within countries, although efforts have been made to improve these areas of health prevention.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the number of blind children living in developing countries within sub-Saharan Africa is disproportionately high. This disparity is due to a combination of factors including supply chain challenges, limited health infrastructure, access to trained subspecialists, and cultural and social factors that may change healthcare-seeking behavior ( 5 ). Immunization and nutritional supplementation, which are critical to childhood vision health, for conditions such as measles and vitamin A deficiency (VAD), respectively, may vary between and within countries, although efforts have been made to improve these areas of health prevention.…”
Section: Introductionmentioning
confidence: 99%
“…Eye Health-Seeking behavior (HSB) can be defined as willful action taken by individuals who have eye problems with the intention of finding a possible solution [1,2]. Behavior being a pattern or way of life could be obvious or hidden traits, that influence a man's attitude toward seeking eye health care through various factors such as socioeconomic factors, psychological behavior of patient is a complex decision-making especially when it comes to the uptake of healthcare interventions, being influenced by the patients' overall engagement with health and healthcare, patient-healthcare provider relationships and previous experiences; and the socio-economic context of decision-making [3][4][5]. Studies in sub-Saharan Africa identified barriers to HSB among adults to include socioeconomic status, masculinity, lack of awareness of the need for primary eye care, cultural beliefs, peer influences, distance and cost, health and illness values, social support, residence and access to health resources, as well as lack of availability of eye care services, lack of awareness about the need and availability of services, financial constraints, utilization of time to receive such services, improper referral by general practitioners and belief in traditional medicine and taboos [6][7][8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…Valuing the voices of those receiving support deserves a greater emphasis within programmes 7 as it can strengthen adaptive programming and improve the quality of services. 8 …”
Section: Introductionmentioning
confidence: 99%